2021
DOI: 10.1002/bse.2908
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of absorptive capacity in the development of circular economy business models of small and medium enterprises

Abstract: Most firms, especially small and medium enterprises (SMEs), find it difficult to integrate circular economy strategies within their business models. Moreover, there is a lack of research on approaches for the successful implementation of circular economies in SMEs in the field of manufacturing. To fill this gap, we investigate the antecedents of absorptive capacity in successful circular economy business cases using a qualitative multiple-case study. Focusing on the horticultural sector, we interviewed six Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 94 publications
1
57
0
1
Order By: Relevance
“…Synthetic, mineral materials (e.g. metals and alloys) flow in technical cycles, meaning that they are conceived to be used in subsequent cycles of production and consumption; biological or renewable materials, instead, return to the natural environment to restore and build natural capital (Ellen MacArthur Foundation [EMF] & McKinsey, 2012; Marucci et al, 2021).…”
Section: Circular Economymentioning
confidence: 99%
“…Synthetic, mineral materials (e.g. metals and alloys) flow in technical cycles, meaning that they are conceived to be used in subsequent cycles of production and consumption; biological or renewable materials, instead, return to the natural environment to restore and build natural capital (Ellen MacArthur Foundation [EMF] & McKinsey, 2012; Marucci et al, 2021).…”
Section: Circular Economymentioning
confidence: 99%
“…In fact, Alonso-Muñoz et al (2021) considered the use of ACAP in the framework of the circular economy, even though they focussed on supply chain management. While Marrucci et al (2021c) limited the analysis on the connections between ACAP and circular economy to a qualitative assessment. To date, most studies have focussed on the relationship between ACAP and environmental, economic and eco-innovation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Govindan and Hasanagic (2018) systematically reviewed the literature in order to identify circular economy barriers, while Ormazabal et al (2018) suggested two different categories of barriers: hard barriers and human‐based barriers. The significant upfront investment cost, the lack of awareness or sense of urgency have been identified as implementation barriers (Marrucci, Iannone, et al, 2021). In addition, Hopkinson et al (2018) demonstrated the need “to develop competencies and capabilities in order to address complex and highly dynamic factors.” Dynamic capabilities could support organisations in the structural changes required to achieve corporate sustainability and circular economy.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%